2013
DOI: 10.1590/s2237-60892013000100009
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid and phospholipase A2 plasma levels in children with autism

Abstract: The study did not show a correlation between fatty acid and phospholipase A2 plasma levels and the developmental profile of children with autism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 19 publications
(25 reference statements)
0
6
0
Order By: Relevance
“…Total n -6/ n -3 LCPUFA ratio was reported in six studies, of which two reported ARA/EPA ratio [ 27 , 52 ], and one reported both ARA/EPA and ARA/DHA also [ 51 ]. Of the remaining studies, two reported the ratio of ARA/EPA [ 28 , 66 ] and ARA/DHA each [ 26 , 30 ], one both [ 53 ], and three no ratios [ 65 , 67 , 68 ]. Reverse ratios and SDs were calculated in five studies ([ 50 ] (only the ARA to EPA) and [ 49 , 51 , 52 , 53 ]).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Total n -6/ n -3 LCPUFA ratio was reported in six studies, of which two reported ARA/EPA ratio [ 27 , 52 ], and one reported both ARA/EPA and ARA/DHA also [ 51 ]. Of the remaining studies, two reported the ratio of ARA/EPA [ 28 , 66 ] and ARA/DHA each [ 26 , 30 ], one both [ 53 ], and three no ratios [ 65 , 67 , 68 ]. Reverse ratios and SDs were calculated in five studies ([ 50 ] (only the ARA to EPA) and [ 49 , 51 , 52 , 53 ]).…”
Section: Resultsmentioning
confidence: 99%
“…Heterogeneity for EPA reduced slightly by removing the Parletta, 2016 study [ 52 ] ( I 2 = 74%, p = 0.0008). Removal of this study together with the Tostes, 2013 study [ 68 ] significantly reduced heterogeneity for EPA ( I 2 = 0%, p = 0.78) that was accompanied by a reduction in the difference between cases and controls (−0.30 [−0.51, −0.08], Z = 2.73, p = 0.006, n = 356). These two studies were different with respect to some characteristics that may affect outcomes compared to other studies; children with ASD were significantly younger than typically developing children in the Parletta, 2016 study [ 52 ], and 88% of children with ASD in the Tostes, 2013 study were on psychotropic drugs [ 68 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously reviewed the genetic and environmental risk factors that cause defects in the signalling of the COX‐PGE 2 pathway and lead to neurodevelopmental disorders such as ASD (Tamiji & Crawford, ; Wong et al ., , ). For example, various studies reported lower levels of arachidonic acid, abnormal levels and activity of PLA2, and increased levels of COX‐2 and PGE 2 in blood plasma of individuals with ASD (Bell et al ., , ; El‐Ansary et al ., ; Tostes et al ., ; Brigandi et al ., ; El‐Ansary et al ., ; Jory, ). These changes were correlated with abnormalities in sensory behaviours of ASD (El‐Ansary et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…22,30,[35][36][37] Various abnormalities in key components of the COX2/PGE2 pathway due to both genetic and environmental influences have been implicated in clinical studies on ASD 20,21 (Figure 1). For instance, increased and decreased ratios of AA to omega-3 and omega-6 fatty acids, [38][39][40] increased PLA2 activity, 41 decreased total AA and increased PGE2 levels 42 have been reported in blood samples of human patients with ASD. Moreover, polymorphism of Ptgs2, the gene that encodes the COX2 enzyme, has been associated with ASD and its relevant behaviors.…”
mentioning
confidence: 99%